Gli sguardi degli altri Filmare il paesaggio urbano come esperienza multi-culturale e multi-identitaria - Pavoni, Raffaele (Strumenti per la didattica e la ricerca, 2019)
The refugee's gaze is always plural and not only able to grasp, but also to promote the different dimensions of culture: an event, a landscape, a human activity unfold in front of their gaze, with the memory of a different environment, far away in time, as a constant background. The first edition of the initiative Filmare l'Alterità (Filming Otherness), created by the SAGAS Department of the University of Florence, was born with a clear goal: to try and represent this gaze through mobile devices and moving images. What we asked foreign citizens living in Florence and in the neighbouring towns was to not to tell us about their life, but about ours, and to do it by starting from the urban landscape.